Amorphous carbon nanotubes-molybdenum disulphide: A potential material for energy storage. (December 2022) - Jain, Kritika; Bhowmick, P.; Das, B.; Sarkar, J.; Gain, A.; Ghorai, U.K.; Chattopadhyay, K.K.; Banerjee, D.
Abstract: Owing to the increasing need for energy generation and storage, here the supercapacitor application of amorphous carbon nanotubes (a-CNTs)-Molybdenum disulphide (MoS2 ) hybrids has been reported. The a-CNT-MoS2 hybrid was developed by a simple solvo-thermal approach at temperature as low as 250 °C. By varying initial reagent two hybrid samples having two different morphologies of MoS2 were prepared and characterized (along with pure a-CNTs) with techniques like X-ray diffraction, electron microscopy and EDX analysis. The optical studies were done by Raman, Fourier transformed infrared, UV-Visible spectrophotometer. Detail electrochemical analysis through cyclic voltmetric study shows that as prepared hybrid samples can be used as an efficient supercapacitor material with specific capacitance 511 F/g at scan rate of 5 mV/second. The material shows high Coulombic efficiency over 1200 cycles and good rate capability thus can be considered to be a promising material for the charge storage application. The surface area and the porosity were considered to be the key parameters for the efficient ion exchange and thus offering higher capacitance values. When compared with existing literature it is seen that our hybrid offers comparable or even better storage performance with the further advantages of low cost high yield synthesis techniques over the existing system. Graphical Abstract: ga1